Digital Transformation and Sustainable Oriented Innovation: A System Transition Model for Socio-Economic Scenario Analysis - Roberto Pasqualino (MDPI AG, 2021)
Sustainability and digitalization are essential duties for companies to perform in the current socio-economic landscape due to risks caused by traditional manufacturing practices, and rules imposed by stakeholders and governments. Tools that help exploring uncertain future scenarios to address such a complex challenge are of vital importance for both businesses, governments, and financial institutions. This paper presents the IN4.0-SD, a novel system dynamics model to capture the dynamic interplay of industrial innovation, inequality, and inflation. The IN4.0-SD is a closed-economy System Dynamics model composed of three agents: sustainable oriented innovation business (SOIB), digital asset supplier business (DASB), and household. DASB and SOIB are both assumed to supply one product to the economy and fundamentally differ among each other in their business models. While the sustainable oriented innovation business produces and sells capital goods making revenue out of sales, digital asset supplier detaches the concept of production from sales moving toward an intangible economy, charging for a fee licence of their tools that can be distributed via a network economy. Simulations show the level of flexibility of the model in addressing a variety of scenarios, playing at the threshold of technology development, inequality rise, massive unemployment and providing an archetype for sustainable oriented innovation and digital transformation models. The findings suggested by the model analysis are used to infer conclusions for the wider society, including implications for sustainable oriented businesses and digital transformation. These are confirmed by previous studies, around the overall trend in wealth creation for large technology firms’ owners, potential impact for employment in the digital economy, and transformation for the labour market.